Gambaran Tingkat Depresi Pada Penderita Congestive Heart Failure (CHF) Di Poliklinik Jantung Rumah Sakit Umum Pusat Dokter Soeradji Tirtonegoro Klaten - Praptiwi, Wanudya Suci; , Arief W. Jadmiko, S.Kep., Ns., M.Kep (2017)
Background: Congestive Heart Failure (CHF) or heart failure is one of the diagnosis of cardiovascular disease the most rapidly increasing in amount. Patients with heart failure are more prone to experience feelings: depression disorder. Depression is a common mental disorder characterized by depressed mood, loss of interest or pleasure, feelings of guilt or low self-esteem, eating disorders or sleep, lack of energy and a low concentration.Objective: This study aimed to describe levels of depression and characteristics (sex, age, education, occupation, income, and stage of disease duration) in patients with heart failure in Clinic Heart Hospital Dr. Soeradji Tirtonegoro Klaten. Methods: This study is a quantitative study with descriptive and analytical approach. The samples in this study were 70 patients with heart failure were obtained by purposive sampling technique. Measuring the level of depression using the scale of the Beck Depression Inventory-II (BDI-II). Results: The results of the univariate analysis obtained from the data of respondents who do not have depression or depression normal 20 respondents (29%), mild depression 38 respondents (54%), depression was 10 respondents (14%), and severe depression 2 respondents (3%), While the characteristics of the respondents showed most respondents are male is 52 respondents (74%), aged 61-70 years 35 respondents (50%), unemployment 32 respondents (46%), secondary school education 30 respondents (43%), monthly income than Rp 1,000,000 29 respondents (41%), long the diagnosis of heart failure is one in 49 respondents (70%), and the stages of most diseases is stage III 30 respondents (43%). Conclusions: Characteristics of patients with heart failure at the Heart Hospital Polyclinic Dr. Soeradji Tirtonegoro Klaten majority of respondents are male, aged over 60 years, unemployment, secondary school education, monthly income than Rp 1.000.000, long diagnosis of heart failure is one year, patients in stage III and depressed levels largely is a mild depression. Keywords: depression, heart failure